A comparative analysis of centralized versus distributed approaches in electrical power generation: a study on furnace oil based power plants of Bangladesh - Mazumder, Fukrul Islam (BARC University, 2018)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2017.